KETIDAKADILAN GENDER PADA ACARA TV SINEMA INDOSIAR: TELAAH PERSPEKTIF STRUKTURASI GIDDENS - Fitrinanda An Nur; Ade Audyana; Rahayu Gurniawati (Jurnal Riset Komunikasi (JURKOM), 2020)
This paper examines the issue of gender injustice in the perspective of Giddens structuration. Cases of this injustice rooted in life, especially in the women's division of labor that would likely put back women in the domestic sphere. This issue is certainly inseparable from the influence of the media as an agent who has the power to shape the thinking of the public, and also the role of the people who have the power in shaping social structures. The media has the power to produce and reproduce a discourse. This research is a descriptive qualitative research method and uses Giddens structuration theory in looking at the role of agents in portraying women in the media. This research focuses on the Indosiar cinema program. This research focuses on the Indosiar cinema program. Results from the study showed women still be the object of oppression and women will return to the domestic sphere, the study also showed that women face with a double burden. If she works in the public sphere, she also continues to work in the domestic sphere. The media perpetuates this through the stories that are displayed.